Controle de erosão, melhoramento das propriedades físicas e aumento da produtividade de podzólico vermelho-amarelo eutrófico pela cobertura morte com bagaço de cana-de-açúcar triturado. - Dantas, Álvaro Barreto (1995)
Soil productivity basically is its ability to oduce crops, being a function of the soil's chemical, physical, and biological properties as well as climate and management. Previous research developed in the coastal zone of Ceará tate has showed that in the lack of conservationist management, high rainfall erosivity associated with moderate to high erodibility of eutrophic Red-Yellow Podzolics predominant in this region have produced serious erosion rates. Consequently , the productivity of this soil is suffering severe reductions through soil, water, organic matter and nutrient losses as well as structure degradion and increasing proximity of crops roots to unfavorable subsoil. The need to develop erosion control techiques and alternative crop and soil management pratices in order to reverse the impact of soil losses on productivity by enhancing its protection, maintaning its structure and impro ing its water retention and availability leaded to this study wich was desinged to e aluate the interrelations between rainfall erosivity and the effects of sugarcane triturated bagasse used as mulch on erosion control of an eutrophic Red Yellov Podzolic soil in Fortaleza (CE); to measure soil productivity and its physical beha iour as related to granulometry, organic matter content, aggregate stability and water economy as a function of this mulch; and to determine cassava and cowpea intercrop yields related to soil management without any conservation pratice and with sugarcane bagasse mulch associated or not to suplementar nitrogen combined with NPK fertilizers. Under exceptionaI rainfall erosivity of 7.407,1 MJ.mm/ha.h the 34 t/ha sugarcane bagasse mulch reduced soiI and water tosses from an average of 47,6 t/ha and 726,8 mm on no mulch pIots to 8,1 t/ha and 346 mm on the mulched treatments. As a consequence of greater water infration and better physicaI and chemical conditions in the mulched management system average yieIds of cassava and cowpea were 26,8% and 40,1 % greater than those in the no muIched systems and 34,6% and 70,2% greater than those determined in the controI pIot without any conservation pratices, respectiveIy. Additional N did not significantly affected crop yieIds but fertilized plots increased production as compared with the controI pIot. Rapid rate of decomposition of the bagasse which decreased from 90% of soil cover in the beginning of the experiment to 39,3% five months after, decreased gradually its effects. WhiIe it was very effective in the most critical period when recentIy tilled soiI had no crop cover, after harvest, siIt and ela content decreased in the topsoil. However, this did not invalidate additional benefits of the muIch which were: organic matter content increases of 42,6% and 43,4% in mulched plots with reference to uncovered treatments and to the control plot, respectively; protetion of good soil structure via dissipation of the kinetic energy of falling raindrops; increase in aggregate stability and mean weight-diameter which was 10,8% greater in the mulched and fertilized plot plus additional N as compared to the uncovered control plot; decrease in soil surface sealing and compaction as evidenced by the aggregation status and higher benefit/cost relation of the infiltrated water and fertilizers as evidenced by the higher biomass and crop yields in the mulched treatments. Considering its expressive amount available in the agroindustries, sugarcane bagasse mulch, might be, depending on the reduction of cost of its transport and distribution, an ecological, effective and economical alternative technology for controlling erosion losses and improving soil conditions for plant growth.